Kartu Interaktif "Ceritain Dong!" sebagai Media Peningkatan Kemampuan Public Speaking Siswa Kelas V SDN 1 Abiansemal Dauh Yeh Cani - Helmy Syakh Alam; Eka Grana Aristyana Dewi; Putu Berliana Suardana Putri; Ni Wayan Arsya Gita Carmela; Ayu Briantari Santi Nadia Putri; Dego Tri Satriyo; Marcello Putra Pasya (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Public speaking is an essential skill that needs to be developed from an early age; however, many elementary school students still lack confidence in expressing their opinions. This community service activity aims to improve students' public speaking skills through interactive learning using the "Ceritain Dong!" card media at SDN 1 Abiansemal Dauh Yeh Cani, involving 28 fifth-grade students. The activity was designed using a descriptive qualitative approach, combining experiential learning and game-based learning principles. The method includes the delivery of basic speaking techniques, ice-breaking sessions, and direct practice through three types of card activities: question cards, challenge cards, and lucky cards. Evaluation was conducted through observation and pretest–posttest assessment using a Likert scale across three indicators: performance courage, self-confidence, and speaking fluency. The results indicate a tendency of improvement in students' abilities, as shown by the increase in the average score from 3.68 to 3.74, along with observable changes in participation, confidence, and clarity in expressing ideas, although the difference was not statistically significant (p = 0.508).